Bioactive compounds in Cucumis melo L. and its beneficial health effects: a scoping review - Ong, Ying Qian; Sakinah Harith; Mohd Razif Shahril; Norshazila Shahidan (Penerbit Universiti Kebangsaan Malaysia, 2019)
Cucumis melo L. possesses numerous medicinal and nutritive functions due to the rich sources of biological active compounds. However, Cucumis melo L. processing generate by-products that threaten the environment. This study aims to explore the bioactive compounds present in different melon parts and the fruit’s beneficial health effects. A methodological framework proposed by Arksey and O’Malley was used to conduct the scoping review. An electronic database search for English academic articles was conducted using PubMed, Scopus and ScienceDirect encompassing years between 1999 and 2019. All types of studies, excluding systematic review or review papers were eligible for inclusion. Out of 602 studies identified, a total of 18 studies were included. Both peels and seeds were rich in phenolic compounds. The seed oil contained rich sources of tocopherols, while β-carotene and vitamin C were found in the flesh. Next, the main beneficial health effects included antioxidant, anti-inflammatory, anti-ulcer, anti-angiogenic, anti-diabetic, anti-bacterial and anti-hypothyroidism activities, which were attributable to the presence of bioactive compounds. In summary, Cucumis melo L., particularly its seeds and peels exhibited various health benefits. This was an indicative of the potential of incorporating these by-products into various food and nutraceutical applications to create novel functional food or dietary supplements.